Activation energy and motile microorganism influence on MHD Jeffery nanofluid with stratifications - M. Siva Sankari; M. Eswara Rao; Waris Khan; O. D. Makinde; Fuad A. Awwad; Emad A. A. Ismail (AIP Advances)
This study investigates the use of reacting and radiating nanofluids to enhance heat and mass transfer in non-Newtonian hydromagnetic bioconvection over a stretching porous vertical plate. It focuses on the combined effects of a magnetic field, Joule heating, porous medium permeability, viscous dissipation, buoyancy forces, thermal radiation, chemical reactions, and the bioconvection of motile microorganisms to prevent the settling of nano entities. The mathematical model transforms the partial differential equations (PDEs) governing the conservation of mass, momentum, energy, nanoparticle concentration, and microorganism density into ordinary differential equations through appropriate similarity transformations. Semi-analytical solutions are obtained using the homotopy analysis method. The effects of various thermophysical parameters on the overall flow structure, including microbial diffusion rates and heat and mass transfer rates, are presented graphically and in tables. Key findings reveal that higher bioconvection Rayleigh numbers and magnetic field intensity reduce the flow rate, while increased thermophoresis and Brownian motion enhance nanofluid temperature profiles. These insights hold significant applications in polymerization, fuel industry, bioengineering, and biomedicine.